Association of MMP2 and MMP9 gene polymorphisms with nonsyndromic cleft lip/palate in an Iranian population - Fatemeh Zahedipour; Hamid Reza Khorram Khorshid; Emran Esmaeilzadeh; Koorosh Kamali; Asghar Ebadifar (Tabriz University of Medical Sciences, 2023)
Background. Cleft lip/palate (CL/P) is a prevalent congenital disorder. Matrix metalloproteinases (MMPs) play a role in palatogenesis and have been proposed to be associated with nonsyndromic CL/P development. This study aimed to examine the association of MMP2 (rs243866) and MMP9 (rs3918242) gene polymorphism with nonsyndromic CL/P in an Iranian population. Methods. Blood samples were collected from 120 nonsyndromic CL/P patients and 140 healthy newborns in this case-control study. DNA extraction was performed by the salting-out method, and the samples underwent polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP), using Pag and SphI enzymes, for genotyping MMP2 and MMP9 gene polymorphisms. Statistical analysis was performed with SPSS 11.5. Univariate and multivariate logistic regression models were used to calculate the odds ratios and 95% confidence intervals (CIs). The level of statistical significance was set at P<0.05. Results. No significant association was found between MMP2 gene polymorphism and nonsyndromic CL/P. However, the MMP9 gene polymorphism had a significant association with nonsyndromic CL/P, with a higher prevalence of the T allele and TT genotype in the case group than the control group. Conclusion. This study indicated a potential link between MMP9 gene polymorphism and nonsyndromic CL/P in an Iranian population. Future investigations with greater sample diversity and larger sample sizes are required to obtain more comprehensive and robust evidence. In-depth analyses and studies involving different ethnic groups can further enhance our understanding of the genetic underpinnings of CL/P.